2013
DOI: 10.4236/aar.2013.21002
|View full text |Cite
|
Sign up to set email alerts
|

Social integration: How is it related to self-rated health?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Generally, women seek company and support from other people more often than men [48]. Consequently, they have larger and more varied social networks, as well as closer relationships [46,51]. In our study, the mediating effect of neglect on SRH among men, not women, can find explanation in the Berkman's Conceptual Model of Social Networks and Health [52].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Generally, women seek company and support from other people more often than men [48]. Consequently, they have larger and more varied social networks, as well as closer relationships [46,51]. In our study, the mediating effect of neglect on SRH among men, not women, can find explanation in the Berkman's Conceptual Model of Social Networks and Health [52].…”
Section: Discussionmentioning
confidence: 56%
“…According to Berkman et al [52], social network influences physical and mental health mainly through social support. It is acknowledged that active daily contact with friends and/or family is positively associated with better SRH among older adults [51]. Caetano et al [46] state that low social support and reduced social network result in less frequent use of health services, poor functional capacity, somatic health problems, and unhealthy behaviors which are all factors influencing health assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Social integration theory suggests well-established health benefits of social relationships for adults. [26,27] Living arrangements refer to individuals' most immediate social environment, which increases the likelihood of accessing resources and seeking instrumental supports from other members living in the same household. [28] Given the interconnectedness between physical and psychological well-being, it can be assumed that availability of resources and supports can influence life satisfaction in a similar way that those resources impact physical health.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…17 In India, according to the WHO Survey on Global AGEING and Adult Health (SAGE) 2007-10, about one in five older adults (19.3%) had symptoms related to depression. Recent studies have revealed that the effect of support from friends on psychological distress among the elderly is stronger than the effect of support from their children and other relatives 21 A growing body of literature shows that for maintaining a healthy life social ties plays a major role. 22 Targeting of socially isolated elderly is an important public health issue.…”
Section: Introductionmentioning
confidence: 99%